Peningkatan Prestasi Siswa di Sekolah Daerah Tertinggal pada Sapta Lomba PAI - Ismail, Heri Taufik; Nursobah, Asep; Erihadiana, Mohammad (Program Studi Pendidikan Agama Islam, Universitas Muhammadiyah Bandung, 2024)
This study aims to analyze the strategy of Islamic Religious Education (PAI) teachers in curriculum development at SDN Girimukti, Cijambe Sub-district, Subang Regency. This curriculum development is faced with new challenges and opportunities that require an innovative approach of PAI teachers in schools and fostering students' talents in achieving achievements. This research used a qualitative approach with a case study method. Data were collected through interviews with PAI teachers and student achievers, observation of curriculum development activities, and analysis of related documentation. The results showed that first, the general description of the curriculum development of SDN Girimukti Cijambe Subang is characterized by evaluative creative style. It is characterized by consistent guidance on student talent. Second, the efforts made involve the use of technology in learning, integration of Islamic values, and fostering student talent through the use of technology. Third, the challenges faced include the lack of financial support and school facilities. Nevertheless, despite the shortcomings and challenges, the efforts to foster students' talents have a positive impact on student achievement. This study concludes that fostering students' talents in obtaining Sapta Lomba PAI achievements by PAI teachers at SDN Girimukti Cijambe Subang is key in developing a curriculum that is relevant and responsive to the challenges of the times.